Sistem Informasi Pemasaran Produk Pada Toko Online Agsel - Gusti Jaya, Suarni; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2022)
The marketing information system at the existing Agsel Online Store still uses a manual system (dor to bang, wa, brochures and facebook), so the product marketing process takes a lot of time, does not update, is not efficient and spends a lot of money to print banners and brochures resulting in high income. accepted by the minimal agsel shop. For this reason, Agsel online shop wants to use web-based marketing to increase revenue, save time because the web can be accessed at any time, is accurate and more efficient. The purpose of this research is to analyze and design a Product Marketing Information System at Agsel Online Stores. The method used by the author is the prototype design method according to the title that the author takes, namely the analysis and design of a marketing information system at the Agsel online store. It is hoped that with this web-based marketing and sales, it can increase revenue at the Agsel store with more and more Agsel store products being known more widely by the entire community. It is hoped that further researchers at the Agsel store can create a website application that can combine product sales predictions with the Weka application and real web creation, not just design.